Immuno-fluorescence Assay of Leptospiral Surface-exposed Proteins - Pinne, Marija (MyJove Corporation, 2011)
Bacterial surface proteins are involved in direct contact with host cells and in uptake of nutrients from the environment (1). For this reason, cellular localization can provide insights into the functional role of bacterial proteins. Surface localization of bacterial proteins is a key step towards identification of virulence factors involved in mechanisms of pathogenicity. Methods for fractionating leptospiral membranes (2-5) may be selective for a certain class of outer-membrane proteins (OMPs), such as lipoproteins vs. transmembrane OMPs, and therefore lead to misclassification. This likely is due to structural differences and how they are associated to the outer membrane. Lipoproteins are associated with membranes via a hydrophobic interaction between the N-terminal lipid moiety (three fatty acids) and the lipid bilayer phospholipids (6, 7). In contrast, transmembrane OMPs are typically integrated into the lipid bilayer by amphipathic β-sheets arranged in a barrel-like structure (8, 9). In addition, presence of a protein in the outer-membrane does not necessarily guarantee that the protein or its domains are exposed on the surface. Spirochetal outer membranes are known to be fragile and therefore necessitate methods involving gentle manipulation of cells and inclusion of sub-surface protein controls to assess the integrity of the outer membrane. Here, we present an immunofluorescence assay (IFA) method to directly assess surface exposure of proteins on intact leptospires. This method is based on recognition of leptospiral surface proteins by antigen-specific antibodies. Herein, antibodies specific for OmpL54(10) are detetcted aftero binding to native, surface exposed epitopes. Comparison of antibody reactivity to intact versus permeabilized cells enables evaluation of cellular distribution and whether or not a protein is selectively present on leptospiral surface. The integrity of outer membrane should be assessed using antibody to one or more subsurface proteins, preferably located in the periplasm. The surface IFA method can be used to analyze surface exposure of any leptospiral protein to which specific antibodies are available. Both the usefulness and limitation of the method depends on whether the antibodies employed are able to bind to native epitopes. Since antibodies often are raised against recombinant proteins, epitopes of native, surface-exposed proteins may not be recognized. Nevertheless, the surface IFA method is a valuable tool for studying components of intact bacterial surfaces. This method can be applied not only for leptospires but also other spirochetes and gram-negative bacteria. For stronger conclusions regarding surface-exposure of OMPs, a comprehensive approach involving several cell localization methods is recommended (10).